2016
DOI: 10.1108/ijoa-01-2015-0840
|View full text |Cite
|
Sign up to set email alerts
|

Impact of workplace characteristics on work-family conflict of dual-career couples

Abstract: Purpose The purpose of this paper is to assess the effects of various workplace characteristics on work-family conflict among dual-career couples in India. Design/methodology/approach Primary data based on 393 employees belonging to dual-career couples were analyzed. Using multiple regression analysis, the study has attempted to find out the effects of workplace characteristics on work-family conflict in dual-career couples. Findings The findings indicate that not all workplace characteristics effect work-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 60 publications
3
28
1
3
Order By: Relevance
“…As predicted it was found that high temporal flexibility was a significant predictor of WFC whereas high operational flexibility was a significant predictor of FWC. Study results are also consistent with the previous studies by Allen et al (2013), Kundu et al (2016), Rastogi et al (2016) and Shockley and Allen (2007). Thus, when mothers perceive higher autonomy over their work schedule they will report less WFC and when they have flexibility where they can complete their work they will report less FWC.…”
Section: Discussionsupporting
confidence: 90%
“…As predicted it was found that high temporal flexibility was a significant predictor of WFC whereas high operational flexibility was a significant predictor of FWC. Study results are also consistent with the previous studies by Allen et al (2013), Kundu et al (2016), Rastogi et al (2016) and Shockley and Allen (2007). Thus, when mothers perceive higher autonomy over their work schedule they will report less WFC and when they have flexibility where they can complete their work they will report less FWC.…”
Section: Discussionsupporting
confidence: 90%
“…Recent research chronicles dual careerism in Australian (Elloy & Smith, 2004), Canadian (Neault & Pickerell, 2005), Indian (Kundu, Phogat, Datta, & Gahlawat, 2016), Nigerian (Ugoani, 2013), and Taiwanese (Wang & Tien, 2011) contexts. The case of Dong and Lin contributes a contemporary Chinese perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Destaca-se que as áreas de Psicologia ;DUMANI et al, 2015). Nos estudos na área de Economia de negócios, exemplos de trabalhos incluem: (1) agenda de pesquisa sobre conflito trabalho-família e emoção por meio de diferentes lentes paradigmáticas (BOCHANTIN; COWAN, 2016); (2) papel da identificação organizacional na redução do conflito trabalho-família em empregos de alto risco como, por exemplo, bombeiros (ALLEN; CROWE; BARAN et al, 2016); e (3) avaliação das características do trabalho e seus efeitos no conflito trabalho-família para casais em que ambos trabalham (KUNDU; PHOGAT;DATTA et al, 2016).…”
Section: áReas Temáticasunclassified
“…Algumas considerações sobre essas combinações são feitas a seguir. A satisfação no trabalho e a satisfação com a vida podem estar relacionadas ao equilíbrio entre os papéis do trabalho e da família bem como com o apoio organizacional, apoio do supervisor e dos colegas de trabalho (PATTUSAMY; JACOB, 2016; ALEGRE; MAS-MACHUCA; BERBEGAL- MIRABENT, 2016;LAMBERT;MINOR;WELLS et al, 2016). Nos casos em que não há satisfação com o trabalho ou essa satisfação é baixa, a intenção de sair do emprego pode aumentar, elevando, consequentemente, a rotatividade.…”
Section: Conflito Trabalho-família E Hot Topicsunclassified